Design and implementation of an autonomous device with an app to monitor the performance of photovoltaic panels (2024)
Photovoltaics (PV) utilize sunlight to generate electricity, thus playing a crucial role in generating clean energy and decreasing carbon emissions. Simultaneously, these systems encourage self-sufficiency in energy production. Consequently, it becomes imperative to monitor the performance of photovoltaic systems as an essential method for assessing and confirming these advantages. Precise measurement and analysis of performance data offer researchers and industry experts valuable insights into system effectiveness, power generation trends, as well as their overall ecological influence. The significance of PV monitoring in ensuring and enhancing system performance is emphasized by the research conducted. The ability to collect and analyze real-time data enables operators to identify inefficient modules, as well as shading or other obstacles that could hinder energy production. Furthermore, monitoring systems enable early identification of potential malfunctions, which allows for timely maintenance and repair actions. Ultimately, these practices enhance overall energy generation while extending the longevity of PV installations. This paper presents the design and implementation of a portable electronic device to measure the I-V and P-V curves of photovoltaic panels. This instrument acquires solar radiation, ambient temperature, electric current, and voltage signals from a PV panel via a cellphone through a mobile application. The device, capable of real-time characterization of PV panels up to 20 A and 500 V, features a 240 MHz Tensilica LX6 dual-core processor and 4 MB of storage memory. Experimental tests were carried out in two different geographical locations in Colombia: the city of Puerto Carreño and the city of Bogotá. Among the main results, an efficiency of 13.29 % was obtained for solar radiation of 755.47 W/m2 and a temperature of 29.60 °C for a monocrystalline PV panel of 405 W.